First Record of Scirtidae (Coleoptera) Associated With Decaying Carcasses in the Neotropical Region - Farias, Rodrigo Cesar Azevedo Pereira; Dal-Bó, Daniel; Santos, Wellington Emanuel dos; Creão-Duarte, Antonio José; Thyssen, Patricia Jacqueline (EntomoBrasilis, 2013)
During a two-year study on the insect fauna associated with pig carcasses in an Atlantic forest remnant in João Pessoa, state of Paraíba, Brazil, 127 adult Scirtes sp. were collected. This is the first record of specimens of the family Scirtidae associated with carcasses in the Neotropical region. Primeiro Registro de Scirtidae (Coleoptera) Associado a Carcaças em Decomposição na Região Neotropical Resumo. Durante um estudo de dois anos da entomofauna associada a carcaças de suínos em um remanescente de Mata Atlântica em João Pessoa, PB, Brasil, foram coletados 127 indivíduos de Scirtes sp. Este é o primeiro registro de exemplares da família Scirtidae associados a carcaças na região Neotropical.